CIP-based analysis on strongly nonlinear interaction between solitary wave and submerged flat plate. (15th March 2019) - You, Rui; He, Guanghua; Wang, Jiadong; Liu, Pengfei
Abstract: A Constrained Interpolation Profile (CIP) based multi-phase numerical viscous wave flume was constructed to investigate extremely nonlinear interaction between solitary waves and a submerged flat plate. Tangent of Hyperbola for Interface Capturing (THINC) scheme was employed to capture the free surface accurately. A total of 12 cases in constant water depth was investigated considering 4 incident wave heights and 3 submergence depths of the plate. Firstly, computational results of the solitary wave profiles, free-surface elevations, and hydrodynamic forces on a flat plate were validated against the published experimental data. Secondly, the evolution process of solitary waves interacting with the flat plate was shown for an intuitive impression. Thirdly, the influence of the incident wave height and submergence depth of the plate on the free-surface elevation and hydrodynamic forces was investigated. The pressure distribution at the time instant when peak force occurred was then presented. Finally, the velocity and vorticity fields containing several strongly nonlinear and interesting phenomena were illustrated and discussed. Highlights: A CIP-based numerical wave flume was constructed to investigate interaction between solitary waves and a submerged plate. Influence of wave height and submergence depth on the free-surface elevation and hydrodynamic forces was investigated. The fluid fields including the pressure distribution, velocity vector and vorticity fields were analyzed and discussed. Accuracy of the numerical model in prediction of the strongly nonlinear wave-plate interaction were validated.